Domestic Violence From a Child Perspective: Impact of an Immersive Virtual Reality Experience on Men With a History of Intimate Partner Violent Behavior - Seinfeld, Sofia (Journal of interpersonal violence, 2023)
Domestic violence has long-term negative consequences on children. In this study, men with a history of partner aggression and a control group of non-offenders were embodied in a child’s body from a first-person perspective in virtual reality (VR). From this perspective, participants witnessed a scene of domestic violence where a male avatar assaulted a female avatar. We evaluated the impact of the experience on emotion recognition skills and heart rate deceleration responses. We found that the experience mainly impacted the recognition of angry facial expressions. The results also indicate that males with a history of partner aggression had larger physiological responses during an explicit violent event (when the virtual abuser threw a telephone) compared with controls, while their physiological reactions were less pronounced when the virtual abuser invaded the victim’s personal space. We show that embodiment from a child’s perspective during a conflict situation in VR impacts emotion recognition, physiological reactions, and attitudes towards violence. We provide initial evidence of the potential of VR in the rehabilitation and neuropsychological assessment of males with a history of domestic violence, especially in relation to children.